2021
DOI: 10.3389/fgene.2021.675587
|View full text |Cite
|
Sign up to set email alerts
|

Global Gene Expression Profiling and Transcription Factor Network Analysis of Cognitive Aging in Monozygotic Twins

Abstract: Cognitive aging is one of the major problems worldwide, especially as people get older. This study aimed to perform global gene expression profiling of cognitive function to identify associated genes and pathways and a novel transcriptional regulatory network analysis to identify important regulons. We performed single transcript analysis on 400 monozygotic twins using an assumption-free generalized correlation coefficient (GCC), linear mixed-effect model (LME) and kinship model and identified six probes (one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…On the contrary, the PDE4D-sparing PDE4 inhibitor ABI-4 did not affect inflammatory processes in murine microglia cultures, excluding a direct role for PDE4D in inflammation (Hedde et al, 2017). Alternatively, PDE4D-specific inhibition has been largely related to improved memory and neuroplasticity (Mohammadnejad et al, 2021;Xiang et al, 2020;Zhang et al, 2017;Shi et al, 2021;Zhang et al, 2014;Sierksma et al, 2014;Cui et al, 2019). However, despite being a therapeutic target, it is hypothesized that especially PDE4D is responsible for the emetic side effects upon pan PDE4 inhibition since PDE4D is highly expressed in the area postrema, the chemoreceptor trigger zone for emesis in the brainstem, compared to other PDE4 genes (Mori et al, 2010).…”
Section: Introductionmentioning
confidence: 93%
“…On the contrary, the PDE4D-sparing PDE4 inhibitor ABI-4 did not affect inflammatory processes in murine microglia cultures, excluding a direct role for PDE4D in inflammation (Hedde et al, 2017). Alternatively, PDE4D-specific inhibition has been largely related to improved memory and neuroplasticity (Mohammadnejad et al, 2021;Xiang et al, 2020;Zhang et al, 2017;Shi et al, 2021;Zhang et al, 2014;Sierksma et al, 2014;Cui et al, 2019). However, despite being a therapeutic target, it is hypothesized that especially PDE4D is responsible for the emetic side effects upon pan PDE4 inhibition since PDE4D is highly expressed in the area postrema, the chemoreceptor trigger zone for emesis in the brainstem, compared to other PDE4 genes (Mori et al, 2010).…”
Section: Introductionmentioning
confidence: 93%
“…Samples were labeled with Cy5, and the reference consisting of a pool of 16 samples was labeled with Cy3. Hybridization, washing, scanning, and quantification were performed according to the array manufacturer's recommendations [20,21].…”
Section: Rna Extraction Gene Expression Analysis and Expression Data ...mentioning
confidence: 99%
“…The PDE4D subtype has shown to be a promising target for memory enhancement. In a recent exploratory study, PDE4D expression in blood was found to negatively correlate with cognitive function in monozygotic twins [ 15 ]. Moreover, PDE4D gene variants affect functional brain networks in patients with mild cognitive impairment and AD [ 16 ].…”
Section: Introductionmentioning
confidence: 99%